2021
DOI: 10.3389/fimmu.2021.648184
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Tissue Damage and Recovery After EV71 Infection Correspond to Dynamic Macrophage Phenotypes

Abstract: Enterovirus 71 (EV71) is a positive single-stranded RNA virus from the enterovirus genus of the Picornaviridae family. Most young children infected with EV71 develop mild symptoms of hand, foot and mouth disease, but some develop severe symptoms with neurological involvement. Limb paralysis from EV71 infection is presumed to arise mainly from dysfunction of motor neurons in the spinal cord. However, EV71 also targets and damages skeletal muscle, which may also contribute to the debilitating symptoms. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…CSF1R is an important pathway for the polarization of M2 macrophages ( 24 ). In addition, the upregulated expression of PTPRC, ITGAM, and ITGB2 in macrophages is also associated with inflammation ( 25 27 ). Our results suggested that the expression levels of hub genes were all elevated in DEP compared to controls, and the ROC curves indicated that TLR4 had a high diagnostic value.…”
Section: Discussionmentioning
confidence: 99%
“…CSF1R is an important pathway for the polarization of M2 macrophages ( 24 ). In addition, the upregulated expression of PTPRC, ITGAM, and ITGB2 in macrophages is also associated with inflammation ( 25 27 ). Our results suggested that the expression levels of hub genes were all elevated in DEP compared to controls, and the ROC curves indicated that TLR4 had a high diagnostic value.…”
Section: Discussionmentioning
confidence: 99%
“…These differences were confirmed when we compared the two groups after an infectious challenge with K. pneumoniae , as differences in the infected groups in the same markers were observed as those seen in the vehicle-treated groups. However, in response to infection, marked differences were also observed in the CMP frequency of CD206, TLR4 and Ly-6C, all of which have important host defense functions ( 27 , 28 , 33 , 34 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hand-foot-and-mouth disease (HFMD) is a common childhood infectious disease, primarily caused by Enterovirus 71 (EV71). In severe cases, HFMD can result in serious neurological complications such as brainstem encephalitis, neurogenic pulmonary oedema, and even death ( Lu et al., 2021 ). EV71 is a single-stranded positive-sense RNA virus, and belongs to the small RNA virus family, genus Enterovirus.…”
Section: Introductionmentioning
confidence: 99%